Akad Kerjasama Usaha Wisata Air Perspektif Hukum Islam - Ayik Dyahsasena; Siti Nurhayati (Program Pascasarjana Universitas Ibrahimy, 2022)
Humans as social beings mean that humans cannot be separated from other people to fulfill all their needs. That cooperation between humans was needed to carry out life. One form of cooperation carried out at Gronjong Wariti Water Tourism, Mejono Village, Plemahan District, Kediri Regency was investment cooperation. The cooperation agreement in this tourism business was carried out in two ways, namely an oral contract and a written contract. In the implementation of the two contracts, both orally and in writing, the pillars and conditions of the contract have been fulfilled. The implementation practice that occurred was the implementation of the mudharabah muqayyadah contract and was included in the sahih mudharabah contract. However, the existence of fraud committed by the contracting parties causes the party to sin because in the mudharabah contract the principle of justice really must be realized.